PRAKTIK PERJANJIAN UTANG ANTARA PETANI DAN AGEN SAWIT DALAM PERSPEKLTIF QARDH DAN URF’ (STUDI KASUS DI KEC. LONGKIP) : (Studi Kasus di Kecamatan Longkip) - Lisnawati, Depi; Arbaina, Mik Imbah (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2023)
Background. This research is motivated by the practice of debt agreements for consumptive and productive needs in the people of Lae Saga Village, Longkip District, Subulussalam City. Aim. This study aims to find out the mechanism of the debt agreement and to examine the views of the qardh and urf contracts on the debt and credit agreements that occurred in Longkip District. Methods. This study uses a type of qualitative research with an empirical approach. The object of this research is the debt agreement. The subjects are palm oil farmers and agents. The data source for this research uses primary data from interviews and secondary data obtained through library research. Results. The results of the study show that the debt agreement is carried out by the people of the sub-district. Longkip occurs because of a sense of trust and awareness to help each other. The implementation of the loan agreement is in accordance with the provisions of the qardh contract. because the pillars and terms of the contract have been fulfilled, so that the practice may be carried out. if it is reviewed based on the customs and habits of local residents, it is included in urf 'sahih because it is a good habit to do.